Social network analysis of Kampung Kuantan Fireflies Park, Selangor and the implications upon its governance - Othman, Mohd. Shahwahid; Mohd Noor, Mohd Iqbal; Amir Mustafa, Amira Mas Ayu; Ibrahim, Rahinah; M. S., Mohd Ihsan (Forest Research Institute Malaysia, 2016)
Community-based management practices stakeholder inclusivity is claimed to be the panacea in overcoming problems and dilemmas in governing ecotourism. Kampung Kuantan Fireflies Park (KKFP) in Kuala Selangor faced several complaints from tourists which were hypothesised to be associated with governance of the park. Social network analysis was utilised to identify the key stakeholders within the governance network of managing ecotourism and in understanding the interests and roles of these stakeholders. The network metrics used were number of edges, density, geodesic distance, and degree and betweenness centralities. The network metric and map obtained suggested that the local community boatmen had the highest degree and betweenness centralities in the KKFP social network. Inclusivity, particularly in the fireflies observation boat ride and tour services, had occurred but involvement in the management decision-making held by the district office could be improved. Possible explanations are provided for the dichotomy of findings between the informal power held by the local community boatmen and the formal authority held by the district office in the context of the Malaysian culture and custom.